Network security architectures - Convery, Sean (Networking technology series, 2012)
This book is part of the Networking Technology Series from Cisco Press, which offers networking professionals valuable information for constructing efficient networks, understanding new technologies, and building successful careers. Whether you are a network or security engineer, Network Security Architectures will become your primary reference for designing and building a secure network. This book discusses the whys and hows of security, from threats and counter measures to how to set up your security policy to mesh with your network architecture.